2006
DOI: 10.1037/0893-3200.20.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Associations between family cohesion and adolescent siblings' externalizing behavior.

Abstract: This study asked whether family cohesion, a measure of whole family functioning, was associated with adolescent siblings' externalizing problems, controlling for the quality of each sibling's relationship with his or her parents. The sample included 93 families (mothers, fathers, and 2 adolescent siblings). Family cohesion was measured from videotaped observations of parents and 2 of their adolescent children discussing family conflict and limit setting. Adolescents reported on hostility in their relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 35 publications
7
56
0
7
Order By: Relevance
“…Thus, the family appears involved in adolescents who display behavioral problems. These results are in accordance with earlier research, for example reporting that family cohesion was negatively associated with adolescents' externalizing problems [38]. Likewise, maternal warmth and overall parental emotional support, in addition to overall neighborhood support, were important predictors of externalizing behavior problems [39].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the family appears involved in adolescents who display behavioral problems. These results are in accordance with earlier research, for example reporting that family cohesion was negatively associated with adolescents' externalizing problems [38]. Likewise, maternal warmth and overall parental emotional support, in addition to overall neighborhood support, were important predictors of externalizing behavior problems [39].…”
Section: Discussionsupporting
confidence: 92%
“…By contrast, adolescents whose early relationships were characterized by negative trust-related experiences (i.e., neglect, trauma, intrusiveness, inconsistency, and inaccurate communication) demonstrate difficulty in coping with distress and relationship conflict (Mikulincer, 1998;Richmond & Stocker, 2006). Moreover, some large scale studies have discovered that relational learning in adolescence is highly influenced by the level of family engagement and perceived emotional availability of family members (Coll, Juhnke, Thobro, Haas, & Robinson, 2008;Trumpeter et al, 2008).…”
Section: Cohesion Vs Conflictmentioning
confidence: 99%
“…Rather, it is the capacity for closeness and reciprocal feelings of empathy within the family system. Richmond and Stocker (2006) suggest that adolescents from families that are emotionally connected, warm, and flexible demonstrate healthy psychological adjustment.…”
Section: Cohesion Vs Conflictmentioning
confidence: 99%
“…Family systems theory posits that families consist of subsystems of relationships and family dynamics are a result of the interaction between these subsystems (Cox & Paley, 1997;Minuchin, 1985). In support of this theory, a number of studies examining family influences on child development have found significant relations between marital, parent-child, and sibling relationships (Cowan & Cowan, 2002;Feinberg & Hetherington, 2001;Kowal, Krull, & Kramer, 2006;Richmond & Stocker, 2006;Stewart, Mobley, Salvador, & Van Tuyl, 1987;Volling, McElwain, & Miller, 2002;Volling & Elins, 1998). More recently, researchers have underscored the importance of whole-family interactions, such as coparenting between mothers and fathers, noting that family influence goes beyond the direct effects of dyadic interaction (McHale, 1995;McHale, Lauretti, Talbot, & Pouquette, 2002;SchoppeSullivan, Frosh, Mangelsdorf, & McHale, 2004;Volling, Blandon, & Grovine, 2006).…”
mentioning
confidence: 86%